Assessment of wind energy resources in Nigeria – a case study of north-western region of Nigeria - Olomiyesan, Boluwaji; Oyedum, Onyedi; Ugwuoke, Paulinus; Abolarin, Matthew (International Journal of Physical Research, 2017)
This study assesses the wind-energyresources in Nigeria by reviewing the existing literature on the subject matter, and also evaluates the wind potential in six locations in the northwest region of the country. Twenty-two years’ (1984 – 2005) wind speed data obtained from the Nigerian Meteorological Agencies (NIMET) were used in this study.Weibull two-parameter and other statistical models were employed in this analysis. Wind speed distribution across Nigeria shows that some locations in the northern part of the country are endowed with higher wind potential than others in the southern part of the country. Moreover, assessment of the wind-energy resources in the study locations reveals that wind energy potential in the region is lowest in Yelwa and highest in Kano; WPD varies from 28.30 Wm-2 to 483.72Wm-2 at 10 m AGL, 45.33 Wm-2 to 775.19 Wm-2 at 30 m AGL and 56.43 Wm-2 to 964.77 Wm-2 at 50 m AGL.Thus Kano, Sokoto and Katsina are suitable for large-scale wind power generation, while Gusau is suitable for small-scale wind power generation; whereas Yelwa and Kaduna may not be suitable for wind power production because of their poor wind potential.